2010
DOI: 10.1093/rheumatology/keq108
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibitors MS-275 and SAHA induced growth arrest and suppressed lipopolysaccharide-stimulated NF- B p65 nuclear accumulation in human rheumatoid arthritis synovial fibroblastic E11 cells

Abstract: In summary, MS-275 and SAHA exhibited their anti-rheumatic activities by growth arrest in RA synovial fibroblasts, inhibition of pro-inflammatory cytokines and NO, as well as down-regulation in angiogenesis and MMPs. Their anti-rheumatic activities may be mediated through induction of p21 and suppression of NF-kappaB nuclear accumulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(104 citation statements)
references
References 48 publications
2
97
3
Order By: Relevance
“…This finding is consistent with reports that HDAC inhibitors MS-275 and SAHA could induce growth arrest and suppress LPS-stimulated nuclear accumulation of NF-κB p65 in human rheumatoid arthritis synovial fibroblastic E11 cells. 31 Furthermore, in the present study, we found that the effect of HDAC inhibition on blocking LPS-induced reduction of Thy-1 protein levels was more apparent at the protein level than at the level of mRNA. Moreover, LPS and HDAC inhibition seemed to disproportionately affect Thy-1 protein expression (Figure 4), implying some indefinite factors, such as posttranscriptional processes, may be involved in the regulation of Thy-1 expression.…”
Section: Discussionsupporting
confidence: 56%
“…This finding is consistent with reports that HDAC inhibitors MS-275 and SAHA could induce growth arrest and suppress LPS-stimulated nuclear accumulation of NF-κB p65 in human rheumatoid arthritis synovial fibroblastic E11 cells. 31 Furthermore, in the present study, we found that the effect of HDAC inhibition on blocking LPS-induced reduction of Thy-1 protein levels was more apparent at the protein level than at the level of mRNA. Moreover, LPS and HDAC inhibition seemed to disproportionately affect Thy-1 protein expression (Figure 4), implying some indefinite factors, such as posttranscriptional processes, may be involved in the regulation of Thy-1 expression.…”
Section: Discussionsupporting
confidence: 56%
“…13,26,27) We found that IL-1b and LPS stimulation increased HDAC1 expression, while emodin remarkably reduced IL-1b and LPS-mediated expression of HDAC1, but not HDAC2, in the …”
Section: Emodin Suppressed Inflammatory Responses Via Inhibition Of Hmentioning
confidence: 77%
“…SAHA, MS-275, as well as other HDAC inhibitors, can induce cyclin-dependent kinases (CDKs) inhibitors p21 and/or p16 which play important roles in cell cycle control and increased cell proliferation (52). Choo et al (47) recently have published that MS-275 and SAHA inhibited human RA synovial fibroblastic E11 cell proliferation in a noncytotoxic manner. The antiproliferative activities were associated with G0/G1 phase arrest and induction of CDK inhibitor p21 (52) 0.…”
Section: Influence On T-cell Differentiationmentioning
confidence: 99%
“…In vivo use of HDACi also inhibited T-cell cytokine production and proliferation and promoted T-cell anergy in conjunction with altered chromatin remodeling of the IL-2 promoter and acetylation of key transcription factors, including NFκB (46,47). Brogdon et al (48) Influence on RA Synovial Fibroblasts Different HDACi have been shown to suppress in vitro proliferation and to inhibit growth and DNA synthesis in RA synovial fibroblasts (41,42).…”
Section: Influence On T-cell Differentiationmentioning
confidence: 99%